1987
DOI: 10.1177/0950017087001002004
|View full text |Cite
|
Sign up to set email alerts
|

The Newmarket Racing Lad: Tradition and Change in a Marginal Occupation

Abstract: This paper describes the work of a widely seen but little known occupation, the racing lad. It relates some changes which have taken place in the organisation of work and the subjective responses to these of a significant minority of the occupation in the locality studied. Such changes as are apparent are accounted for in terms of developments in the local labour market which have served to erode the traditionalist framework within which work has been organised. At root, the core activity is seen to depend on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The racing industry was already experiencing a labour shortage [20], with concerns over retention and recruitment previously high prior to lockdown [5]. Prior to the pandemic, trainers already highlighted that finding staff cover was a main source of stress, in part due to a current staff shortage in racing [5,6,[20][21][22], and thus the current circumstances are likely to exacerbate ongoing staffing issues. A recent report suggested that nearly half (46%) of stable staff surveyed are concerned about job security [23].…”
Section: Impact On Uk Horseracingmentioning
confidence: 99%
“…The racing industry was already experiencing a labour shortage [20], with concerns over retention and recruitment previously high prior to lockdown [5]. Prior to the pandemic, trainers already highlighted that finding staff cover was a main source of stress, in part due to a current staff shortage in racing [5,6,[20][21][22], and thus the current circumstances are likely to exacerbate ongoing staffing issues. A recent report suggested that nearly half (46%) of stable staff surveyed are concerned about job security [23].…”
Section: Impact On Uk Horseracingmentioning
confidence: 99%
“…Research by Filby [11] identified other significant changes that were having an effect on the organisation of work in racing yards. These included, for instance, the introduction in the late 1970s of a national minimum wage for racing staff, which meant trainers found themselves having to adapt their labour processes rather quickly once a national minimum wage had to be paid.…”
Section: Staff Shortages and Changes In The Organisation Of Work Imentioning
confidence: 99%
“…The once ready supply of cheap labour (indentured apprentices) stopped (see Butler [12] for a more detailed explanation of indentured apprenticeship). Other factors played their part: a declining workforce lured by the opportunities available of alternative better-paid employment, an increase in the size and weight of the population and an increase in the number of horses in training [6,11]. In 1975, there were 11,491 horses in training; this has now risen to over 16,000 in 2018 [6,13] which, coupled with the introduction of Sunday racing in the 1990s [14], an increase in the fixture list from 1132 meetings in 2000 to 1508 in 2018 [6,13,15], a greater regulation in the hours stable staff can work and overtime payment, [9] has meant staff and trainers are constantly under pressure.…”
Section: Staff Shortages and Changes In The Organisation Of Work Imentioning
confidence: 99%
See 1 more Smart Citation